2009
DOI: 10.1088/0960-1317/19/3/035028
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent mechanical properties of polydimethylsiloxane membranes

Abstract: Polydimethylsiloxane (PDMS) has cross-linked network structures and its properties have been regarded as dimensionally independent. Here we demonstrate that both the mechanical strength and the Young's modulus of the PDMS membranes are thickness dependent and the transition from bulk behavior to dimension dependent is predicted to occur at a membrane thickness of about 200 μm. The thickness-dependent phenomenon is attributed to shear stress during fabrication, which is proportional to the thickness-induced reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
198
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(218 citation statements)
references
References 17 publications
20
198
0
Order By: Relevance
“…As a result, determining the linear elastic properties (i.e., Young's modulus and Poisson ratio) of the PDMS top wall for our three data sets was challenging. In particular, several studies [40,38,39] have shown that the Young's modulus E and Poisson ratio ν s of PDMS strongly depend on the method of fabrication and parameters such as the curing temperature, the specimen thickness and the mixing ratio of the components of the polymeric solution. This dependence, in turn, can result in a typical variation of E = 1 to 3 MPa and ν s = 0.4 to 0.5.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, determining the linear elastic properties (i.e., Young's modulus and Poisson ratio) of the PDMS top wall for our three data sets was challenging. In particular, several studies [40,38,39] have shown that the Young's modulus E and Poisson ratio ν s of PDMS strongly depend on the method of fabrication and parameters such as the curing temperature, the specimen thickness and the mixing ratio of the components of the polymeric solution. This dependence, in turn, can result in a typical variation of E = 1 to 3 MPa and ν s = 0.4 to 0.5.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…For the present analysis, the variation in the Poisson ratio has been neglected and PDMS has been modelled as a nearly incompressible solid (ν s = 0.499). Raj and Sen [13] have used a value of E = 1.362 MPa, based on experimental results from [39], for their theoretical calculations. However, knowing the sensitivity of the Young's modulus to curing conditions, we made an attempt to find the particular curing conditions under which Liu et al [39] have reported their measurements.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5(c)) and we find R = 0.8 mm. For PDMS ν = 0.5; the Young modulus depends on the thickness of the membrane and for 30µm it is about E = 1.4MPa 37 . For these values one finds a = 5.8 µm and P b = 6 kPa.…”
Section: B Cyclic Actuation Below the Explosion Thresholdmentioning
confidence: 99%
“…By comparison, PDMS has a tensile Young's modulus in the range of 1.32-2.97 MPa, slightly higher than that of skin [33][34][35]. It is proved that compatible component can endow the polymer blend improved mechanical properties [36].…”
Section: Resultsmentioning
confidence: 96%